Advanced Biomimetic Nanomaterials for Non-invasive Disease Diagnosis - Feng, Zhiyuan; Fan, Hao; Cheng, Lin; Zhang, Huan; Fan, Hong; Liu, Jia (Frontiers in Materials, 2021)
In modern society, the incidence of cancer, inflammatory diseases, nervous system diseases, metabolic diseases, and cardiovascular diseases is on the rise. These diseases not only cause physical and mental suffering for patients, but also place an enormous burden on society. Early, non-invasive diagnosis of these diseases can reduce the physical and mental pain of patients and social stress. There is an urgent need for advanced materials and methods for non-invasive disease marker detection, large-scale disease screening, and early diagnosis. Biomimetic medical materials are synthetic materials designed to be biocompatible or biodegradable, then developed for use in the medical industry. In recent years, with the development of nanotechnology, a variety of biomimetic medical materials with advanced properties have been introduced. Biomimetic nanomaterials have made great progress in biosensing, bioimaging, and other fields. The latest advance of biomimetic nanomaterials in disease diagnosis has attracted tremendous interest. However, the application of biomimetic nanomaterials in disease diagnosis has not been reviewed. This review particularly focuses on the potential of biomimetic nanomaterials in non-invasive disease marker detection and disease diagnosis. The first part focuses on the properties and characteristics of different kinds of advanced biomimetic nanomaterials. In the second part, the recent cutting-edge methods using biosensors and bioimaging based on biomimetic nanomaterials for non-invasive disease diagnosis are reviewed. In addition, the existing problems and future development of biomimetic nanomaterials is briefly described in the third part. The application of biomimetic nanomaterials would provide a novel and promising diagnostic method for non-invasive disease marker detection, large-scale clinical screening, and diagnosis, promoting the exploitation of devices with better detection performance and the development of global clinical public health.